2015
DOI: 10.2147/ppa.s67171
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about missed contraceptive pills among married women at King Abdulaziz University Hospital

Abstract: BackgroundOral contraceptive pills (OCPs) are one of the most reliable methods of contraception. However, lack of knowledge about oral contraceptive use and inconsistent pill-taking might result in decreased efficacy. The study reported here aimed to explore women’s knowledge about oral contraceptive use and assess the factors associated with knowledge about OCPs among users.MethodsThis cross-sectional survey was conducted at King Abdulaziz University Hospital, Jeddah, Saudi Arabia between April and June 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
2
19
0
3
Order By: Relevance
“…The researcher found seven studies covered all type of contraceptive methods [4,6,8,9,10,11,12]. Also, eleven studies focused on one or two types of contraceptives that were commonly used in SA [6,13,14,15,16,17,18,19,20,21,22].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The researcher found seven studies covered all type of contraceptive methods [4,6,8,9,10,11,12]. Also, eleven studies focused on one or two types of contraceptives that were commonly used in SA [6,13,14,15,16,17,18,19,20,21,22].…”
Section: Methodsmentioning
confidence: 99%
“…Twelve studies were found that assessed women's knowledge about contraceptive methods [4,6,8,11,12,15,16,18,20,22,23,24]. Knowledge of contraceptive methods is summarized in (Table 3).…”
Section: Knowledge About Contraceptive Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also lacked knowledge about withdrawal bleeding during OCP use. They pointed out to primary health care providers; including physicians, nurses, and pharmacists, responsibility to counsel patients to understand OCP instructions [11].…”
Section: Introductionmentioning
confidence: 99%